Genetic Variation in Coat Colour Genes MC1R and ASIP Provides Insights Into Domestication and Management of South American Camelids - Marin, JC (2018)
This research was supported by FONDECYT, Chile Grant 1140785, Postdoctoral Grant 3050046 and CONICYT Chile (Beca de Apoyo a Tesis Doctoral), Morris Animal Foundation (D05LA-002), Darwin Initiative for the Survival of Species (United Kingdom) 1312 grant 162/06/126, The British Embassy (Lima), NERC 1313 (United Kingdom) grant GST/02/828, and Newton Fund Researcher Links Travel grant (ID: RLTG9-LATAM-359537872) funded by the UK Department for Business, Energy and Industrial Strategy and CONCYTEC (Peru) and delivered by the British Council.